Coming of Age in Chinese Literature and Cinema (Amsterdam University Press, 2025)
With the inclusion of twelve original articles by established and emerging international scholars, this volume offers critical reading of literary and cinematic texts produced in China and Sinophone communities between the 1950s and 2010s. The articles portray the lineage and mutations of the Chinese Bildungsroman, providing insights into the tensions between individual and society; nation and the world; and the multiple social, ecological, and virtual realities of recent decades. Concerned with how coming-of-age narratives have persistently returned and evolved over time, the book addresses themes such as family and social change; gender, class, and generational divides, local/global politics, and the ecological and posthuman turns in Chinese/Sinophone culture. It offers a fresh look on how the transnational and transgenerational journeys of Bildungsroman and coming-of-age narratives continuously transform and reinvigorate generic conventions, to explore adolescence as a formative social force and aesthetic experience in Chinese/Sinophone literature and film.